2017
DOI: 10.1007/s11269-017-1604-y
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Peak Flow Rates for Small Drainage Areas

Abstract: Runoff plots are important for soil loss measurements, and increasing numbers of plots use automatic equipment. To choose equipment with appropriate capacities, the peak flow rate must be known. The peak flow rate is also an important parameter in the modified universal soil loss equation (MUSLE) which calculate the soil loss from upland slope. The available peak flow rate equations are primarily for the watershed scale, not for small drainage areas like runoff plot. This study's purpose was to derive an equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This power law scaling was chosen to represent aspects of fluvial landscapes that may control local habitat, such as discharge and channel width (Hicks, 2003;McGarvey & Hughes, 2008;Vannote et al, 1980). Stream discharge typically increases with drainage area with a scaling exponent of 0.5 to 1 (Di Lazzaro & Volpi, 2011;Liu et al, 2017;Ogden & Dawdy, 2003), while published values for a scaling exponent between drainage area and channel width range from 0.3 to 0.5 (Montgomery & Gran, 2001;Wolman, 1955). However, sensitivity tests we performed suggest that in our implementation of the NCM, the number of species simulated within individual drainage basins, and in the landscape as a whole, is not sensitive to the value of b.…”
Section: Neutral Community Model (Ncm) 221 Ncm Backgroundmentioning
confidence: 99%
“…This power law scaling was chosen to represent aspects of fluvial landscapes that may control local habitat, such as discharge and channel width (Hicks, 2003;McGarvey & Hughes, 2008;Vannote et al, 1980). Stream discharge typically increases with drainage area with a scaling exponent of 0.5 to 1 (Di Lazzaro & Volpi, 2011;Liu et al, 2017;Ogden & Dawdy, 2003), while published values for a scaling exponent between drainage area and channel width range from 0.3 to 0.5 (Montgomery & Gran, 2001;Wolman, 1955). However, sensitivity tests we performed suggest that in our implementation of the NCM, the number of species simulated within individual drainage basins, and in the landscape as a whole, is not sensitive to the value of b.…”
Section: Neutral Community Model (Ncm) 221 Ncm Backgroundmentioning
confidence: 99%
“…The peak flow was an important parameter to express the intensity of soil erosion or water loss on steep slopes [56]. In this study, the results in Table 1 indicated that with the increase of rainfall intensity and the concentration of precipitation, the blocking effect of different underlays on surface runoff decreased.…”
Section: Differences In the Impact Of Different Spatial Pattern Of Cypress Micro-topography And Rainfall Conditions On Peak Flowmentioning
confidence: 62%
“…In North America and the North Pacific, land and sea surface temperatures, precipitation, and storm tracks are determined mainly by atmospheric variability associated with the Pacific North American (PNA) pattern. The modern instrumental record indicates a recent trend towards a positive PNA phase, which has resulted in increased warming and snowpack loss in northwest North America (Liu et al 2017 ). This study used fifteen climate mode indices to increase the diversity.…”
Section: Methodsmentioning
confidence: 99%